2018
DOI: 10.3856/vol46-issue1-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization in the distribution of larval fish assemblages during winter and autumn in the Gulf of California

Abstract: ABSTRACT. Larval fish composition and abundance were analyzed during February-March (winter) and November-December (autumn) of 2005 to investigate which environmental conditions and mesoscale oceanographic processes affect the distribution of larval fish assemblages in the Gulf of California, and if these variables and processes are useful to delimit specific regions of ichthyofaunal distribution. The overall pattern was mostly a latitudinal gradient of the abundance of two faunistic complexes of larval fish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Long‐term monitoring efforts in transition zones between tropical and subpolar regions have shown that physical conditions, such as sea surface temperature, are key predictors of larval community composition. Furthermore, physical changes in these environments alter the larval composition of the community (Ahlstrom, 1969 ; Netburn & Koslow, 2018 ; Sassa et al., 2004 ; Urias‐Leyva et al., 2018 ). Aceves‐Medina et al.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term monitoring efforts in transition zones between tropical and subpolar regions have shown that physical conditions, such as sea surface temperature, are key predictors of larval community composition. Furthermore, physical changes in these environments alter the larval composition of the community (Ahlstrom, 1969 ; Netburn & Koslow, 2018 ; Sassa et al., 2004 ; Urias‐Leyva et al., 2018 ). Aceves‐Medina et al.…”
Section: Discussionmentioning
confidence: 99%